Taenia multiceps coenurosis in Tanzania: a major and under‐recognised livestock disease problem in pastoral communities. (9th February 2019) - Hughes, Ellen C; Kibona, Tito K; de Glanville, William A; Lankester, Felix; Davis, Alicia; Carter, Ryan W; de Jong, Rosanne M F; Nyasebwa, Obed M; Claxton, John R; Cleaveland, Sarah; Allan, Kathryn J
Abstract : Abstract A neurological syndrome of small ruminants, known locally as ' ormilo ', has been reported among pastoralist livestock keepers in Tanzania. This study was carried out in four affected pastoral communities to determine the prevalence and associated risk factors, characterise the clinical signs and investigate the aetiology of the syndrome. Questionnaires were administered at all households (n=480) within four study villages. Overall, 94 per cent of households reported at least one case in the previous 12 months. By village, the individual‐level 12‐month period prevalence ranged from 11 per cent to 34 per cent, equivalent to about 10, 000 small ruminants across the four villages. Thirty‐eight households were randomly selected for further investigation. Proprioceptive deficits and weakness were the most commonly observed clinical signs in affected animals. Brain and spinal cord cysts consistent with Taenia multiceps infection were detected in 32 (82 per cent) of 39 affected animals selected for postmortem examination. Feeding small ruminant brains to dogs was identified as an important risk factor for the syndrome, even in households that did not own dogs. This study confirms cerebral coenurosis as a major cause of small ruminant neurological disease in northern Tanzania and highlights the urgent need for further investigation to quantify the disease burden and to identify and implement control measures.